Assessing community and ecosystem sensitivity to climate change – toward a more comparative approach. (March 2017) - Smith, Melinda D.; Wilcox, Kevin R.; Power, Sally A.; Tissue, David T.; Knapp, Alan K.
Abstract: Plant communities can vary widely in their sensitivity to changing precipitation regimes, as reported by Byrne et al., Mulhouse et al. and Sternberg et al. in this issue of Journal of Vegetation Science . But to understand why communities differ in their sensitivity, we argue that clearly defined metrics of sensitivity and coordinated research approaches are needed to elucidate mechanisms. Abstract : Plant communities can vary widely in their sensitivity to changing precipitation regimes, as reported by Byrne et al., Mulhouse et al., and Sternberg et al. in this issue of Journal of Vegetation Science . But to understand why communities differ in their sensitivity, we argue that clearly defined metrics of sensitivity and coordinated research approaches are needed to elucidate mechanisms.